2011
DOI: 10.1080/09658211.2011.602086
|View full text |Cite
|
Sign up to set email alerts
|

Peer influence on event reports among adolescents and young adults

Abstract: When two or more people witness an event together, the event report from one person can influence others' reports. In the current study we examined the role of age and motivational factors on peer influence regarding event reports in adolescents and young adults. Participants (N=249) watched a short video of a robbery then answered questions with no co-witness information or with information believed to be from a co-witness. Public and private response conditions were included to explore motivations for peer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 52 publications
1
14
0
2
Order By: Relevance
“…Like the DRM, memory conformity studies have a well‐established experimental protocol to manipulate false memory production (for a review, see Wright, Memon, Skagerberg, & Gabbert, ). Moreover, this paradigm has been used to produce false memory effects in children, adolescents, and adults (e.g., Candel, Memon, & Al‐Harazi, ; McGuire et al, ; Wright, London, & Waechter, ). Memory conformity research examines the effect of post‐event information on event reports when peers are the source of post‐event information, which sometimes includes misinformation.…”
Section: Memory Conformity and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the DRM, memory conformity studies have a well‐established experimental protocol to manipulate false memory production (for a review, see Wright, Memon, Skagerberg, & Gabbert, ). Moreover, this paradigm has been used to produce false memory effects in children, adolescents, and adults (e.g., Candel, Memon, & Al‐Harazi, ; McGuire et al, ; Wright, London, & Waechter, ). Memory conformity research examines the effect of post‐event information on event reports when peers are the source of post‐event information, which sometimes includes misinformation.…”
Section: Memory Conformity and Developmentmentioning
confidence: 99%
“…Adolescents have been almost wholly ignored in the eyewitness testimony literature (McGuire, London, & Wright, ), with scores of developmental studies instead focusing on young children. Up until the 1980s, child competence statutes generally excluded the testimony of youth on the grounds that young children's testimony is unreliable (Brainerd & Reyna, ; Bruck & Ceci, ; Goodman, ).…”
mentioning
confidence: 99%
“…Due to a number of high‐profile child sexual abuse cases in the 1990s (see Ceci & Bruck, ), most research on children's suggestibility has focused primarily on preschoolers and children under 12‐years‐old (e.g., Powell, Roberts, Ceci, & Hembrooke, ). Literature on adolescent suggestibility remains scarce (McGuire, London, & Wright, ) and has focused largely on interrogative suggestibility. The evidence shows that this age group is at risk for involuntary and false confessions in interrogations (Kassin, Appleby, & Perillo, ).…”
Section: False Memory Research With Adolescentsmentioning
confidence: 99%
“…For example, using a postevent misinformation paradigm, 16‐ to 18‐year‐olds reported fewer misled details than 7‐ to 9‐year‐olds but were as accurate as older adults (60‐ to 85‐year‐olds; Coxon & Valentine, ). Also, McGuire et al () found peer influence affects 11‐ to 25‐year‐olds' memory reports because they were less accurate when cowitnesses provided false (versus true) suggestions, regardless of age. Other studies using semantic association tasks (e.g., Deese–Roediger–McDermott) with 11‐ to 25‐year‐olds showed that false memory actually increased with age (McGuire, London, & Wright, ).…”
Section: False Memory Research With Adolescentsmentioning
confidence: 99%
“…O contato que a criança mantém com os pais ou outras testemunhas entre o período em que testemunhou o crime e o período em que é entrevistada poderá também infl uenciar a narrativa da criança (Principe & Schindewolf, 2012). Desta forma, o contato entre testemunhas deve ser evitado e cada uma delas entrevistada o mais rapidamente possível (McGuire, London, & Wright, 2011).…”
Section: Como Entrevistar Crianças E Adolescentes? -Aspetos Geraisunclassified